M2 macrophages regulate KDM6B/PFKFB2 metabolic reprogramming of cervical squamous cell carcinoma through CXCL1: M2 macrophages regulate CESC - Yu, Jing; Huang, Longzhang; Cao, Lihua (Cellular and Molecular Biology, 2024)
Macrophages in the tumor microenvironment can polarize into M1 or M2 forms, with M2 macrophages (M2φ) promoting tumor growth and metastasis in cervical squamous cell carcinoma (CESC). This study explored the effects of M2φ on CESC metabolic reprogramming both in vitro and in vivo. Results showed that M2φ secreted CXCL1, which significantly increased CESC migration and metabolic regulation. Further experiments revealed that CXCL1 upregulated KDM6B to enhance PFKFB2 transcriptional activity, thus regulating CESC glucose metabolism. Transcriptome sequencing screened 5 upregulated genes related to glycolysis, with PFKFB2 showing the most significant increase in cells treated with rCXCL1. Dual-luciferase reporter assay confirmed that rCXCL1 enhances PFKFB2 transcriptional activity. Bioinformatics analysis revealed a high correlation between expressions of KDM6B and PFKFB2 in CESC. Mechanistic experiments demonstrated that KDM6B inhibited H3K27me3 modification to activate PFKFB2 transcriptional expression. In conclusion, M2φ secreted CXCL1 to promote CESC cell migration and invasion, and CXCL1 activated KDM6B expression in CESC cells, inhibiting H3K27 protein methylation modification, and enhanced PFKFB2 transcriptional activity to regulate CESC glucose metabolism. These results provided new insights into the complex interplay between the immune system and cancer metabolism, which may have broader implications for understanding and treating other types of cancer.